2016
DOI: 10.1002/ps.4474
|View full text |Cite
|
Sign up to set email alerts
|

Using Calendula officinalis as a floral resource to enhance aphid and thrips suppression by the flower bug Orius sauteri (Hemiptera: Anthocoridae)

Abstract: C. officinalis can be used to increase available resources for natural enemies used in agricultural crops, notably in greenhouses. This study also provides evidence that increasing floral resources can enhance pest suppression provided by O. sauteri. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…Our results confirm the usefulness of using banker plants in order to conserve predators during crop-free periods and ensure an early and quick crop colonization soon after transplant. Calendula officinalis has also been shown to contribute to the establishment of other predators in greenhouses (Zhao et al, 2017). Such open rearing units ensure predator persistence in the crop at low pest populations (Messelink et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the usefulness of using banker plants in order to conserve predators during crop-free periods and ensure an early and quick crop colonization soon after transplant. Calendula officinalis has also been shown to contribute to the establishment of other predators in greenhouses (Zhao et al, 2017). Such open rearing units ensure predator persistence in the crop at low pest populations (Messelink et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of these predators often increase as pear psyllid density increases . Like other Orius species, Orius sauteri (Poppius) (Hemiptera: Anthocoridae) is a generalist predator in Asia that feeds on a variety of arthropod prey including mites, thrips, etc . O. sauteri is also a zoophytophagous predator that engages in some modest level of plant feeding alongside its insect prey .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Like other Orius species, Orius sauteri (Poppius) (Hemiptera: Anthocoridae) is a generalist predator in Asia that feeds on a variety of arthropod prey including mites, thrips, etc. 27,28 O. sauteri is also a zoophytophagous predator that engages in some modest level of plant feeding alongside its insect prey. 29 Importantly, O. sauteri is one of the most abundant predators in pear orchards in Beijing (Zhang XC, 2013), and O. sauteri is able to feed on 2 nd to 5th nymphal instars of C. chinensis (Yang and Li) (Hemiptera: Psyllidae) according to our field and laboratory studies (Ge Y, unpublished, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological engineering has been studied in several crop systems and has been shown that strategies to conserve natural enemies can improve pest management (Wäckers et al 2007;Lundgren et al 2009;Simpson et al 2011;Gurr et al 2004Gurr et al , 2012aGurr et al , 2015Balzan et al 2014;Jamont et al 2014;Maselou et al 2014;Zhu et al 2014;Lu et al 2015). The studies revealed the importance of honeydew, nectar and pollen as food sources to enhance adult longevity and reproductive rate and dispersal of natural enemies van Rijn 2005, 2012;Irvin et al 2007;Winkler et al 2009a;Biondi et al 2016;Tena et al 2016;Zhao et al 2017).…”
Section: Introductionmentioning
confidence: 99%